BIOMECHANICAL DIAGNOSTIC SCREENING AS AN IMPERATIVE FOR PERSONALIZING PREVENTIVE AND CORRECTIONAL PROGRAMS FOR INDIVIDUALS WITH FUNCTIONAL MUSCULOSKELETAL DISORDERS - Demokhin, D. Yu.; Kovalchuk, L. V.; Lutskyi, V. Ya. (Rehabilitation and Recreation, 2025)
Introduction. Contemporary empirical studies unequivocally confirm that the biomechanical regularities of the spatial organization of body links are crucial for the effective control of the organism’s interactions with the environment. Such control is vital for preserving somatic health, optimizing physical development, and establishing adequate conditions for individual life activity.The aim of the study is to substantiate and develop individual SMART goals for the personalization of preventive and correctional programs, based on objective quantitative indicators of the biogeometric profile of posture obtained through high-precision biomechanical screening of women.Methods. The research methods included: theoretical analysis and generalization of literary sources; photography and postural analysis; and methods of mathematical statistics.Results. The current societal challenges facing Ukrainian citizens and specialists in the field of physical culture and sports rehabilitation and health fitness necessitate research into and improvement of correctional and preventive work with individuals experiencing disorders in the biomechanics of spatial body organization.The effective development of correctional and preventive measures for individuals with musculoskeletal biomechanical dysfunction requires the application of an integrated, multifactorial paradigm. This paradigm mandates the obligatory integration of the following elements: the methodology of the International Classification of Functioning, Disability and Health for the precise definition of correctional and preventive intervention domains; SMART goal-setting principles for structural organization, ensuring objective result measurability, and dynamic progress tracking; personalization based on the analysis of individual needs, the biogeometric profile of posture, and the characteristics of the individual’s motor activity.Conclusions. A comprehensive quantitative biomechanical analysis of posture identified structural and functional dysfunctions, specifically: increased thoracic kyphosis associated with muscle-tonic imbalance (hypertonus of m. pectoralis minor and hypotonus of mm. rhomboid minor et major), forward head posture, and lower limb biomechanical disorders (varus leg deformity and valgus foot deformity).In light of these data, the personalization of correctional and preventive measures is a decisive condition for achieving efficacy in women with postural disorders. The central mechanism of individualization is goal-setting using the SMART methodology. This approach ensures structured management, guarantees the measurability of screening results, and serves as the foundation for achieving defined functional out-comes.